Global research hotspots and trends on robotic surgery in obstetrics and gynecology: a bibliometric analysis based on VOSviewer - Xiao, Peichen; Li, Lu; Qu, Jinfeng; Wang, Guangxin (Frontiers in Surgery, 2024)
Objective: Over the last two decades, the quantity of papers published in relation to robotic surgery in obstetrics and gynecology has continued to grow globally. However, no bibliometric analysis based on VOSviewer has been performed to evaluate the past and present of global research in the field. In this study, we aimed to analyze the bibliometric characteristics of papers on robotic surgery in obstetrics and gynecology to reveal research hotspots and trends in this field.The Web of Science Core Collection was searched for scientific papers on robotic surgery in obstetrics and gynecology published between January 1, 1998 and December 31, 2023. Bibliometric metadata of each selected paper was extracted for analysis. The results were visualized by VOSviewer (version 1.6.18).Results: A total of 1,430 papers met the inclusion criteria. The United States had the highest total link strengths and contributed the most papers (n = 793). The Mayo Clinic produced the largest number of papers (n = 85), and Professor Pedro T Ramirez contributed the most papers (n = 36). The number of citations ranged from 0 to 295 with a total sum of 29,103. The Journal of Minimally Invasive Gynecology published the most relevant papers (n = 252). Keywords were classified into six clusters based on co-occurrence data, of which cluster 1, cluster 4 and cluster 6 had more main keywords with the largest average publication year.Conclusions: This is the first VOSviewer-based bibliometric analysis of robotic surgery research in obstetrics and gynecology. The United States was the leading country, and the Journal of Minimally Invasive Gynecology was the most productive journal in the field. Scientists and institutions from around the world should push their boundaries to bring about deep collaboration. The main research topic has always been the use of robotic surgery in the treatment of gynecologic malignancies. More randomized controlled trials need to be conducted to compare surgical outcomes of robotic surgery with other surgical approaches. Robotic sacrocolpopexy for pelvic organ prolapse has become a new research hotspot, and robotic surgery for sentinel lymph node detection in gynecologic malignancies are more potential directions for future research.